Universal mobility modeling and its application to interface engineering for highly scaled MOSFETs based on first-principles calculation - Ishihara, T.; Matsushita, D.; Kato, K. (2009 IEEE International Electron Devices Meeting (IEDM), 2009)
We have constructed universal mobility modeling that can treat both the elastic and inelastic scattering due to the polarized dipole. We have confirmed the scheme for the case of the inversion layer mobility. We have performed the interface engineering to improve the mobility degradation due to the interface states based on the universal mobility modeling. We have newly proposed oxygen-termination method based on the finding that oxygen-termination can suppress the inelastic scattering owing to the O atom and efficiently suppress the amount of the interface states. Mobility calculation has shown that oxygen-termination can improve the mobility degradation due to the interface states. Our experimental result has actually confirmed the prediction by our calculation. This fact indicates that the appropriate oxidation process can improve the mobility. Therefore, the construction of oxygen-passivation is the inevitable subject on process engineering for MOSFETs with highly scaled gate oxide.